(untitled) (Global Journal of Medical Research, 2024)
Introduction Dermatological teleconsultation requires patients to provide high-quality images of cutaneous lesions for accurate diagnosis and treatment Patients assume a pivotal role in teledermatology by effectively documenting skin lesions using standardized photographs This study aimed to develop and validate a digital guide to assist patients in adequately documenting cutaneous lesions for dermatological teleconsultations Methods Applied developmental research methods were employed in this study Bibliographic research was conducted to determine the requirements for high-quality photographic documentation for dermatology These investigative findings were adapted into a digital guide for patients using simple and accessible language Subsequently the digital guide underwent validation by dermatologists and laypeople through questionnaires using a five-point Likert scale and statistical analysis to assess reliability and concordance regarding its content and purpose Results After selecting twenty articles the digital patient guide was developed It was based on photographic documentation orientations tailored for primary care physicians due to the lack of materials directed at patients Reliability analysis revealed Cronbach s alpha coefficients of 0 945 for laypeople and 0 718 for experts The concordance analysis of dermatologists questionnaires yielded an intraclass correlation coefficient of 0 79 95 CI 0 48 0 95 Median Likert scale scores were 4 81 for dermatologists and 5 0 for laypeople Conclusions This study successfully developed a digital patient guide for clinical photography of cutaneous lesions The validation process which involved dermatologists and laypeople confirmed consensus and acceptance of the digital guide highlighting its potential practical utility